Teaching research methodology in an online ODL environment: strategies followed and lessons learnt - De Beer, M; Van der Westhuizen, S; Bekwa, N N; Petersen-Waughtal, M; Van Zyl, L. E.; Sadiki, M (South African Journal of Higher Education, 2016)
This article provides an overview of an open distance learning (ODL) honours online research methodology module. The module was developed to address the requirements of the Department of Higher Education and Training (DoHET) for the new Programme Quality Mix (PQM) Honours degrees. This semester module involves 15 active weeks of learning, culminating in the submission of a Portfolio of Evidence summative assessment task. Specific features of the module are described to illustrate how teaching the content was approached in an ODL context. The aim of the approach followed was to enhance student motivation, while maintaining consistent progress in achieving the required learning outcomes throughout the semester. Initial results and student feedback are presented.